2016
DOI: 10.1371/journal.pone.0162594
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Activity of ARQ 087, a Novel Inhibitor Targeting FGFR Dysregulation

Abstract: Dysregulation of Fibroblast Growth Factor Receptor (FGFR) signaling through amplifications, mutations, and gene fusions has been implicated in a broad array of cancers (e.g. liver, gastric, ovarian, endometrial, and bladder). ARQ 087 is a novel, ATP competitive, small molecule, multi-kinase inhibitor with potent in vitro and in vivo activity against FGFR addicted cell lines and tumors. Biochemically, ARQ 087 exhibited IC50 values of 1.8 nM for FGFR2, and 4.5 nM for FGFR1 and 3. In cells, inhibition of FGFR2 au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 54 publications
2
65
0
2
Order By: Relevance
“…Preclinical activity of ARQ-087 was tested in a group of different cancers cell lines showing positive relation between ARQ-087 concentration and cancer cell death (Hall et al, 2016). Currently there are not a lot of data on this drug but the latest studies have shown specific activity inducing cell cycle arrest and apoptosis correlated to the level of FGFR2, a clinical development plan including a patient selection strategy is defined and the drug is currently in a Phase I/II clinical trial (NCT01752920).…”
Section: Arq-087mentioning
confidence: 99%
“…Preclinical activity of ARQ-087 was tested in a group of different cancers cell lines showing positive relation between ARQ-087 concentration and cancer cell death (Hall et al, 2016). Currently there are not a lot of data on this drug but the latest studies have shown specific activity inducing cell cycle arrest and apoptosis correlated to the level of FGFR2, a clinical development plan including a patient selection strategy is defined and the drug is currently in a Phase I/II clinical trial (NCT01752920).…”
Section: Arq-087mentioning
confidence: 99%
“…Preclinical and phase I studies have suggested that these compounds have potent and selective anti-tumor activity against FGFRmutated cancers (80)(81)(82)(83). A recently developed monoclonal antibody against FGFR2 (BAY1179470) showed tumor suppressive potential in tumors with high FGFR2 expression (84).…”
Section: Fgfr2 Fusionsmentioning
confidence: 99%
“…The precise reason for the higher ARQ 087 levels is incompletely understood, and may be due to alterations in the absorption and metabolism of the combined agents. In addition, this may be the cause for the increased toxicity observed in the animals dosed with both compounds; however it is notable that ARQ 087 concentrations as high as those observed in the combo group have been seen in previous xenograft studies without any increased toxicity 28. The toxicity data suggests that continuous dosing of both agents may be suboptimal.…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies, we have demonstrated that ARQ 092 and ARQ 087 as single agents suppressed tumor growth in the AN3CA xenograft model 6,28. Mice bearing AN3CA tumors were treated with various doses of ARQ 092 and ARQ 087.…”
Section: Resultsmentioning
confidence: 99%